Reflection seismic study of the post-glacial Burträsk fault: Cross-dip stack - Juhlin, Christopher; Beckel, Ruth (Uppsala University, 2019)
In 2008, a 22 km long high resolution reflection seismic profile was acquired over the Burträsk fault in Northern Sweden. The Burträsk fault formed at the end of the last glacial, triggered by the rapid melting of the Scandinavian ice sheet and the following crustal rebound. The aim of the survey was to image the structure of the fault with depth. The profile followed existing roads resulting in a very crooked acquisition geometry. A list of the key acquisition parameters is given below.
The dataset was first processed and published in 2011. In 2018, the dataset was reprocessed using an additional cross-dip correction step to improve the imaging of reflection with a dip component in the cross-profile direction. The following data files are available for downloading:
1) raw shot gathers (decoded and quality controlled, with geometry information in the headers)
2) original stacked section from Juhlin and Lund (2011)
3) cross-dip corrected stacked section from Beckel and Juhlin (2019)
4) cross-dip corrected migrated section from Beckel and Juhlin (2019)
A short summary of the main processing steps for each dataset is given below. For a complete description, please refer to the above mentioned publications.

Key acquisition parameters:
Number of channels: 280
Near offset: 0 m
Geophone spacing: 20 m
Geophone type : 28 Hz single
Nominal source spacing : 20 m
Source type : VIBSIST
Hit interval between hammer blows : 100-200 ms
Sweeps per source point :3-4
Nominal fold : 140
Recording instrument : SERCEL 408L
Sample rate : 1ms
Field low cut : Out
Field high cut : 400 Hz
Record length : 23 s
Profile length : 22 km
Source points : 799
Dates acquired: 2008/08/05-2008/08/16

Short summary of the main processing steps:
1) BUR_shots_geom.sgy
The raw shot records are pre-processed with VIBSIST decoding, quality control. Information about the shot and receiver geometry has been added to the trace headers.
2) BUR_original_stack.sgy
The processing flow of the original data stack includes trace editing and balancing, spectral equalization, time-variant bandpass filtering, refraction and residual statics, horizontal median filtering, NMO correction, DMO correction, stacking and coherency filtering (for a complete description see Juhlin & Lund, 2011)
3) BUR_crossdip_stack.sgy
The main processing steps of the crossdip stack are very similar to those of the original stack, including trace editing and balancing, spectral equalization, time-variant bandpass filtering, refraction and residual statics, horizontal median filtering, NMO correction, DMO correction, stacking and coherency filtering. Before DMO correction, an additional cross-dip correction step has been added. For a complete description see Beckel & Juhlin, 2019.
4) BUR_crossdip_mig.sgy
The processing flow of the migrated section includes trace editing and balancing, spectral equalization, time-variant bandpass filtering, refraction and residual statics, horizontal median filtering, NMO correction, cross-dip correction, DMO correction, stacking, coherency filtering and migration (for a complete description see Beckel & Juhlin, 2019).

This dataset contains the cross-dip stack of the Burträsk profile (Beckel & Juhlin, 2019).
Processing steps for this data set:
1. Read decoded VIBSIST data
2. Bulk static shift to zero time
3. Apply geometry
4. Manual first-break picking
5. Trace balance: 0-3000 ms
6. Ground-roll and first-break muting in local time-
frequency domain: 25 % threshold
7. Spectral equalization: 30 Hz window,
25-40-120-150 Hz bandpass
8. Time-variant bandpass filtering:
0-200 ms: 35-60-120-180 Hz
250-500 ms: 30-50-120-180 Hz
600-900 ms: 25-40-110-165 Hz
1100-3000 ms: 20-35-100-150 Hz
9. Refraction statics: floating datum, replacement velocity
from model
10. Trace editing
11. Horizontal median filter: 11 traces, 5300 m s-1 and
3000 m s-1
12. Butterworth filter: 20-40-90-120 Hz
13. Spherical divergence correction: 0.8 tpower, 2.0 vpower
14. Velocity analysis
15. NMO correction: 40 % stretch mute
16. Residual statics
17. Cross-dip correction: 5400 m s-1 , 20 % taper;
Velocity analysis
18. DMO correction;
Velocity analysis
19. Stacking
20. FX deconvolution: 19 trace window
21. Trace balance

Processed seismic data stored as one file for the entire seismic profile, according to SEG technical standard SEG-Y revision 1 (SEG-Y_r1.0, 2002); https://seg.org/Publications/SEG-Technical-Standards

Reflexionsseismiska mätningar över Burträsk-förkastningen I norra Sverige

År 2008 gjordes en reflexionsseismiska undersökning över Burträsk-förkastningen I norra Sverige. Förkastningen formades vid slutet av sista istiden när glaciärerna nedsmältade snabbt. Ändamålen av undersökningen var att avbilda förkastningens djupa strukturerna. Seismisk profilen följde befintliga vägar, vilket resulterade I en ganska slingrig geometri av profilen. Datasetet bearbetades och publicerades först av Juhlin & Lund (2011). I 2018 gjordes ett nytt bearbetning av som omfattade en ytterligare steg för att korrigera effekten av 3D profilgeometrin (Beckel & Juhlin, 2019).

En mer detaljerad beskrivning av datasetet som inkluderar alla viktiga parametrar är tillgängligt på den engelska katalogsidan:https://snd.gu.se/en/catalogue/study/SND1099

Utförlig beskrivning av datasetet finns på den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/SND1099
Reflexionsseismiska mätningar över Burträsk-förkastningen: Cross-dip stack
Keywords: EARTH SCIENCE; SEISMIC PROFILE; fault; fel; geophysics; geofysik; Geology; Geologi; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Geoscientific Information; Geovetenskap